Sistema georreferenciado rastreador de foco da dengue via dispositivo móvel - Martins, Renan Vieira (2014)
Dengue has been being one of the mainly issues of the public health in Brazil and worldwide. According to the World Health Organization about 50 to 100 million people in over 100 countries except from Europe are infected annually. Small and big Brazilian cities are suffering from this disease as an effect of the accelerated urbanization and the weather aspects. This study aims to contribute with combating dengue with a georeferenced system composed by a mobile app using the Android platform and web for tracking the mosquitos outbreaks.